Myanmar as an Investment Destination: A Regional Evaluation - Md Abdullah, Abu Yousuf (Journal of Business and Technology (Dhaka), 2017)
Once considered a pariah state because of its military regime, Myanmar has been taking giant strides towards becoming one of the most promising countries for investing in business ventures. At a time when the global economic scenario is reeling from Britains exit from the European Union, foreign investment in Myanmar continues to attain unprecedented growth. Lifting of international sanctions, a promising economic outlook with a GDP growth rate averaging close to 8% and a sizeable labor force have attracted overseas investment in diverse sectors like energy, manufacturing, power generation, and construction. The country still faces formidable challenges in developing basic infrastructure, ensuring fiscal stability and curbing sectarian conflict. For the nascent democratic government, formulating and implementing effective policies are uphill tasks in a system fraught with bureaucratic inefficiencies, systemic corruption, and interference from the still-powerful military. Myanmar has ample opportunities to overcome internal roadblocks by utilizing its huge market with a predominantly young population, its expansive pool of low-cost labor and the heightened influx of international commercial ventures after the political transition of the mid-2010s. Investments in Myanmars promising telecommunications sector, in ready-made garment manufacturing and in the tourism industry are projected to give substantial dividends over the next few decades. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 11-39